Bahasa Indonesia Bahasa Indonesia - Putu Artawan (Jurnal Penelitian Pendidikan IPA, 2023)
This research aimed at describing the difference of the students learning achievement between-group investigation learning model and conventional learning model, describing the difference of the studentâ€™s learning achievement between mastery goal orientation and performance goal orientation, describing the interaction effect of learning model and goal orientations on learning achievement. The population of this research was VIII grade of Junior high school students. The population member consisted of 296 students. The sample was chosen for 4 classes by group random sampling. The research used a quasi-experimental with pretest-posttest nonequivalent control group design. The data were collected by two kinds of tests; they are questionnaires for goal orientations and objective tests for learning achievement. Learning achievement data were analyzed by descriptive statistics and ANCOVA 2 Ã— 2 where the pretest scores were as a covariant. Further action after ANCOVA, the least significant difference (LSD) was used. Results of this research showed that: there was a significant difference of the students learning achievement between-group investigation learning model and conventional learning model (F = 135.568; p < 0.05); there was a significant difference of the students learning achievement between mastery goal orientation and performance goal orientation (F = 23.522; p < 0.05); there was no significant interactive effect between learning model and goal orientations on learning achievement (F = 0.118; p > 0.05).